A szóolvasási készség online mérésére kidolgozott adaptív és lineáris tesztrendszer összehasonlító hatékonyságvizsgálata - Magyar, Andrea; Molnár, Gyöngyvér (Magyar Pedagógia, 2015)
During the first years of primary education, language development plays a significant role, as children are unable to perform well in schoolwithout suitable reading ability.A paper-and-pencil diagnostic test system was developed by József Nagy in the 1990s to diagnose students’ word reading ability. The spread of computers and the useof computer-based assessment have provided us witha number of new opportunities and made it possible to renew the paper-and-pencil test system by using various advantages of online testing, such as objective administration and scoring, rapid response time, immediate feedback, cheaper data-collection and adaptive testing. The aim of this paper was to explore and quantify the advantages of electronic testing and study the media effect by making detailed comparisons of test results delivered by different media. In this paper, we: (1) outline the original diagnostic assessment system for word reading ability; (2) compare 1st–5th-grade students’ achievement in PP and CB mode; (3) outline the potential for improvement in the system; and (4) present the renewed online adaptive assessment system for word reading abilities. The original paper-and-pencil test system was converted into a computer-based format, the online test system was delivered via the eDia platform, and the data collection was carried out via internet using computer facilities available at schools. The pilot sampleinvolved154 primary school children between grades 1 and 5. A partial credit model was used to scale the items. According to the results, the online version of the test system was suitable for assessing the children’s word reading ability. The person separation reliability of the test was 0.88. The difficulty parameters of the items were spread over a wide range (349–855), making the test suitable for a wide range of abilities. The research represented a promising step towards more precise educational assessment in using computerised adaptive testing among young children.